Storytelling through Picture Description to Enhance Very Young EFL Learners' Oral Production - Diana Elizabeth Arguello San Martin; Maria Rossana Ramirez-Avila; Irma Guzman (Journal of Foreign Language Teaching and Learning, 2020)
This study aimed at improving oral development in the primary school of Ecuador, where teaching English at an early age focuses mainly on expanding reading and writing as productive skills. The purpose of this action research was to individually examine how the use of storytelling through picture description as visual support could benefit communicative skills among a group of second-grade students from a private school in Guayaquil. The study considered vocabulary, organization, and fluency as the basis of oral development using quantitative and qualitative instruments. A pre and post-A1 level speaking assessment measured the improvement of vocabulary and fluency. Results showed that there was an improvement of four points in the descriptive statistics (minimum, maximum and mean). The paired T-samples test revealed the study was highly reliable with a score of p = 0.000. There are few studies related to teaching English as a foreign language in early education worldwide and South America. In Ecuador, no studies were found. Therefore, the implications of this study are addressed to school authorities and other EFL teachers to upgrade the proficiency of their students from early grades.